THE CORRELATION BETWEEN VENTILATION SPACE, HUMIDITY, SUNLIGHTING, DENSITY OF OCCUPANTS, AND NUTRITIONAL STATUS WITH ACUTE RESPIRATORY INFECTION SUFFERED BY CHILDREN ONE TO FIVE YEARS OLD AT MOJOSONGO VILLAGE, SURAKARTA CITY IN 2005. - Margo Utomo; F. Tri Hastuti (JURNAL LITBANG, 2007)
Bockground:There were 72,27 % of acute respiratory infection cases in Sibela Public Health Center, Kalurahan Mojosongo in 2004. In addition, there were 49 % houses at the end of December 2004 which were not qualified for living, there were: not enough ventilation space, few sunlighting coming in the house, too density of occupant, and lack of nutrition for children one to five years old.Purpose : to find out the correlation between ventilation, huntidity, sunlighting, density of occupants, and rutritional stahrs and acute respiratory infection suffered by children oneto.five years old in Mojosongo village, Surakarta City..Method : The study uses eksplanatory research by surveying method, interviewing by giving questionairs, observation and measttring by case control design.The population are 66 babies at 12 to 59 months old who came in Sibela Public Health Centt